Devastation of Earth: an Ecocriticism Study in Cormac McCarthy’s The Road - FAHMI LEKSONO (LITERA KULTURA : Journal of Literary and Cultural Studies, 2013)
Abstrak Karya sastra merupakan miniatur dari dunia nyata, dimana sebuah karya sastra biasanya mengungkap beberapa masalah yang berkaitan dengan makhluk hidup termasuk isu-isu tentang hubungan manusia dengan alam. Manusia lebih cenderung melakukan kerusakan pada lingkungan daripada menjaganya, hal ini menyebabkan kehancuran bumi beserta isinya. Hal ini tergambar pada novel The Road karya McCarthy dimana lingkungan yang menjadi setting utamanya hancur berantakan. Lansekapnya tertutup oleh abu yang berterbangan. Dan ketika salju turun, ia berwarna abu-abu. Langitnya juga terlihat gelap. Oleh sebab itu, ada beberapa masalah yang berhubungan dengan kehancuran bumi yang tergambar pada novel yang kemudian memunculkan dua dasar pertanyaan (1) bagaimana kehancuran bumi digambarkan dalam novel The Road karya McCarthy? Dan (2) bagaimana kehancuran bumi memberikan dampak terhadap karakter utama dalam novel The Road karya McCarthy?. Untuk melihat masalah ini perlu teori yang pas yang biasa disebut ecocriticism. Ecocriticism melihat kehancuran bumi sebagai hasil dari tingkah laku manusia terhadap lingkungan misalnya: eksploitasi dan colonialisasi. Seperti yang dikatakan Lawrence Buell bahwa kondisi lingkungan itu ditentukan oleh manusia. Ecocriticism adalah suatu istilah yang berada dibawah payung postcolonialism dimana seorang postcolonialist meyakini bahwa kolonialisasi mempunyai campur tangan dalam penghancuran bumi. Para penjajah merasa percaya diri untuk mengeksploitasi bumi karena dianugrahi kekuatan oleh modernism. Untuk mendapatkan analisis yang jelas, skripsi ini menggunakan metode descriptive quality dimana kualitas data menjadi poin utama daripada jumlah data. Jadi, terlihat jelas bahwa kehancuran bumi terjadi diseluruh lapisan lingkungan; yaitu atmosfer, permukaan tanah, dan laut. Seluruh atmosfer dipenuhi oleh abu, debu dan karbon, tanahnya terkikis, tandus dan gundul, dan lautnya berubah menjadi abu-abu. Kehancuran bumi ini juga memberikan kesuraman tersendiri kepada tokoh si bapak dan si anak. Mereka harus melalui hidup yang keras, susah untuk bernafas, susah untuk menemukan sesuatu yang bisa dimakan dan secara mental mereka selalu takut akan ancaman-ancaman dari kehancuran bumi. Kata Kunci: kehancuran bumi, ecocriticism, postcolonialism, modernism. Abstract Literary work is a miniature of larger world or reality, whereas a literary work reveals some problems related to humans being including issues of human relationships with the environment. Humans tend to do damage to the environment rather than maintaining it, thus it causes devastation of earth. It is reflected in McCarthy’s the road where the environment is devastated. The landscape save the ash on the wind, and when the snow falls, it is gray. The sky is also dark. Therefore, there are some problems of knowledge about how the devastation of earth portrays in the novel, which are delivered to two main questions of (1) How is devastation of earth depicted in Cormac McCarthy’s The Road? and (2) How does devastation of earth give impacts to the main characters in Cormac McCarthy’s The Road?. In case to observe these problems, it needs a suitable theory which called ecocriticism. Ecocriticism sees the devastation of earth as the result of humans’ behaviour such as exploitation and colonialism of the environment, as Lawrence Buell says that the condition of the environment is determined by humans. Ecocriticism is under umbrella term of postcolonialism in which postcolonilist believes that colonization has intervention in devastating the earth. Colonizer is encouraged to exploit the nature because of power that is given by modernism. To get a clear analysis, this thesis uses descriptive quality method; it means the quality of the data becomes the reference to work rather than the quantity of the data. Thus, it is seen clearly that devastation of earth happened in the whole layers of environment; atmosphere, land and sea. The atmosphere is occupied by ash, dust and carbon, the land has eroded and barren and the sea have changed into gray. This devastation also gives a misery to the father and the son as the main characters. They have to undergo hard life; hard to breathe, hard to find food and mentally they are haunted by the devastated earth’s threatens. Keywords: devastation of earth, ecocriticism, postcolonialism, modernism. INTRODUCTION Humans often feel indifferent toward nature. For them, nature is something considerably as a ‘mystic’ thing, when it goes right, humans forget it, when it goes wrong, they worry it. People tend to prefer natural environments more than built environments, and built environments with water, trees, and other vegetation more than built environments without such features (Kaplan & Kaplan, 1989). On the other word, humans tend to permit the nature walks down by itself. They seem to just let it flow without thinking how to keep and maintenance the nature. The study of humans’ relation with nature which is known as ecology was begun since years ago when humans lived in harmony with the nature. However, in line with development the nature also changes. Unfortunately, this natural changes brings devastation on earth, as Donald Hughes says that looking back to our historical ecology, Humans have related in multiple ways to the Earth’s systems; some of these ways promise a sustainable balance with them, while others are destructive (Hughes, 2001: 269). Historically, through devastation of earth Humans have made major changes in their environments. This is happened almost in the whole surface, as Hughes says that devastation of earth has happened in every historical period and in every part of the inhabited Earth (2001: 1). In order to observe those processes of change that affect the relationship, ecologist studies the mutual effects that other species, natural forces, and cycles have on humans, and the actions of humans that affect the web of connections with non-human organisms and entities (id. at 4.). This ecologist’s study shows that devastation of earth is the result of humans’ behaviour toward environment. This bad behaviour has changed the environment that will bring devastation to the humans themselves. Humans seemingly don’t care of the environment. Severity, humans tend to be more destructive. It forces some Ecocritics who concern in literary study and environment in late nineteenth criticized humans’ behaviour toward nature. This criticises show how important avoiding that kind of behaviour toward nature which brings devastation of earth merely, it signed that the study of literature which related to the environment has to be discussed. There were in fact some isolated calls for an ecologically oriented criticism during the 1970s (Rigby, vol 2: 2). However, it was not until the end of the twentieth century that the study of literature and the environment was finally recognized as ‘a subject on the rise’. In studying of literature, humans ordinarily focus on the relation between humans and others (society) or between humans and themselves (psychology), whereas, the relation between humans and environment actually is tightly connected. Unfortunately, the study of literature which related to the earth was often forgotten, whereas, the study of literature which related to the environment is greatly important. The study of environment is not merely observing of the nature or nonhumans aspect but it tends to study the relation among nature, earth and the humans themselves. Human actually is a part of environmental system, and therefore the environment has the crucial role in humans life in which it is become the main point of literary study. In some respects, it is perhaps not surprising that the study of literary texts should be coupled with such forgetfulness of the earth. Thus it is needed a study of humans’ relation and environment. The study of literature and environment got a full attention when modern era begun to destruct the environment. Since last decade ago, especially years ago, humans consciously realized the impacts of their behaviour toward nature, moreover when they become crazier of invention, exploration and exploitation of the nature. Surely, this impact is indirectly causing ecological changes. However, actually what people do about their ecology depend on what they think about themselves in relation to things around them. Human ecology is deeply conditioned by beliefs about our nature and destiny (White 1996, 6). It can be imagined when humans were only thinking about themselves and forgetting the nature or they were just considering their needs without considering the nature needs, it can be ascertained that the nature will vanish and be extinct. This idea or thought about indifference toward nature is criticized by the Ecocritics. Ecocriticism maintains that literature may be approached in a way that examines humans as part of an ecosystem; they are neither master nor slave to it, but simply one part of an intricate system. Literature and environment truly can’t be separated each other. Moreover, Lawrence Buell argues in his book The Truth of Ecology as quoted by Dana Philip that literature would be environmental. It would evoke the natural world through verbal surrogates, and would thereby attempt to bond the reader to the world as well as to discourse (Philip, 2003: 7). It can be assumed that through the literary work, the reader will be brought to the environmental world and devastation of earth. Indirectly, literature causes the reader’s interpretation of the environment. Thus, it is important to understand the relation between humans and environment through literary work. It needs to notice that ecology is not a slush fund of fact, value, and metaphor, but a less than fully coherent field with a very checkered past and a fairly uncertain future (Philip, 2003: 45). By understanding the relation between humans and environment, it is beneficial to determine the act effectively on the impact of natural destruction and to integrate knowledge and actions. The study of literature and environment works in tandem in determining humans’ perception and interpretation toward nature. As Lawrence Buell says that literature and environment studies must make their case for the indispensableness of physical environment as a shaping force in human art and experience, and how such an aesthetic works (2001: 9). It can be assumed that environmental interpretation is a humanistic inquiry. In other word, what people think about nature, and how they have expressed those ideas is what people interpret of the nature. Generally what people expressed the idea of the nature is a Realistic depiction of the world. Thus, it needs a tool to see this depiction. Surely Ecocriticism is a proper tool to see the depiction of the world. Ecocriticism is the most suitable binoculars to telescoped ecological issue and ecological changes in such literary work, as Sheryl Glotfelty (1996: xviii) says that Ecocriticism is the study of the relationship between literature and the physical environment, Ecocriticism takes an earth-centered approach to literary studies. Only Ecocriticicism observes the relation between humans and nonhumans aspects. What Ecocritics do, in short, is attempting to discover nature as absence, silence in texts, and construe environmental representation as a relevant category of literary (Buell, 2005: 30). Ecocriticism encourages the changing of canonisation through entering literary works which carry up natural issue. Ecocriticism ecologically oriented critique of the way in which Nature is constructed in certain canonical texts. Environmental literature constitutes the third way in which Ecocriticism recasts the canon. According to Lawrence Buell (1995, 7-8), an environmentally oriented work should display some characteristics; first, the nonhuman environment is present not merely as a framing device but as a presence that begins to suggest that human history is implicated in natural history. Second, the human interest is not understood to be the only legitimate interest. Third, Human accountability to the environment is part of the text’s ethical framework. The last, some sense of the environment as a process rather than as a constant or a given is at least implicit in the text. In such literary work; Cormac McCarthy’s The Road the nature as the setting represents ecological changes. Surely, this change causes devastation of earth. Nothing is more miserable on earth but devastation. The world which is the closest place we live at is not convenient again when it was devastated. Thus, literary and environment has interrelation that cannot be separated. Then, it is important to analyze such literary work through Ecocriticism. Ecological issue commonly represented by the presence of natural thing such as; tree, land and also circumstance in the novel which it become the setting. In other word, ecological issue become a centre point of setting. One of great writers in narrating the setting is Cormac McCarthy. Not only known as a king of the setting, McCarthy also has known as famous environmental setting as Addy Haddock (a writer of McCarthy’s bibliography) says that his ability to provide eloquent descriptions with smoothly rolling darker undertones and poetically dismal nuances makes him become a writer with powerful setting. Thus, McCarthy is a right author referenced as a study of Ecocriticism. Indirectly, McCarthy’s proficient is caused by his settled at a barn near Louisville, Tennessee. All the stones he gathered, all the wood he cut and kiln dried by himself to renovate his small house. Seemingly, McCarthy’s life is not far away from the nature. Years later, after marrying fellow student Lee Holleman in 1961, he and she moved to a shack with no heat and running water in the foothills of the Smoky Mountains outside of Knoxville. These experiences of life sharpen his idea toward nature. McCarthy reveals that he is not a fan of authors who do not deal with issues of life and death; it can be assumed that his writing tends to be explored issues of life including devastation of earth. Recalling blithely the months he spent without electricity in a house in Tennessee. Without money, and he had run out of toothpaste and he was wondering what to do when he went to the mailbox and there was a free sample. It made him become more sensitive facing the nature and more respect it. In 2006, McCarthy writes The Road that grants him a change to be interviewed by Oprah Winfrey. Surely, this interview related to his writing especially devastation of earth and won Pulitzer Prize for fiction. McCarthy told Winfrey that related several stories illustrating the degree of outright poverty he endured at times during his career as a writer. He also states that his novel; The Road inspired when he was standing at the window of a hotel in the middle of the night, his son asleep nearby, he started to imagine what El Paso might look like 50 or 100 years in the future. He just had this image of these fires up on the hill. It shows the condition of the nature at the time which the hill was fired up. McCarthy can be categorized as a weird person. People usually gathered with other people who have same hobby or pleasure. However, it doesn’t apply for McCarthy. As a writer, he doesn’t like to gather with other writer. He would rather hang out with physicists or scientist than other writer. He does not know any writers and much prefers the company of scientists. No doubt if his knowledge of nature is rich. His knowledge of the natural world is vast and includes many of the Latin names of birds and animals. His pleasure gathering with physicists and scientist caused by his interest in science and environment, by absorbing the intelligence scientists, he realizes that in 100 years the human race won't even be recognizable. For him, what physicists did in the 20th century was one of the extraordinary flowerings ever in the human enterprise, which would much prefer to befriend a scientist than another writer. Most of McCarthy’s novels are portraying about life or reality which many of them associated to ecological issue. In 1985, Blood Meridian was published. Blood Meridian portrays the desolate and indifferent 1850s Texas-Mexico borderlands. The extreme violence which takes place comments implicitly on both the environment and human nature. The novel’s full title- Blood Meridian, or The Evening Redness In The West- is indicative of the novel’s portrayal of the environment. A relationship between location, nature and violence is created in the symbolism of the sun as a “blood meridian”. To call McCarthy’s environments as constructed in Blood Meridian simply violent is an unsatisfactory conclusion. What is more appropriate and evident in the text is that man is inherently violent and the indifference of nature to this creates an amoral setting. In 1979, McCarthy published his fourth novel, Suttree. In short, Suttree tells the reader about a man named Cornelius Suttree, a fisherman, disillusioned scholar, alcoholic, nihilist, existentialist and transcendentalist. The attention to detail identified earlier in Suttree is telling in terms of his relationship with his environment. Generally, to an Ecocritical reading Suttree shows that, stripped of societal anthropocentrism, man is forced to reassess his relationship with nature. It could be said that McCarthy’s prose style is often atavistic (anti-civilization, anti-materialism, anti-industrialism, anti-progress and pro-Nature) in that it both reflects natural processes and often appears primitive, stripped of culture. In 1973, Child of God was published. It was inspired by actual events in Sevier County. Child of God begins with Lester Ballard’s dispossession from his parent’s house. McCarthy’s description of Ballard’s lone nomadic wandering after he inadvertently burns down his squat uses the same free indirect discourse. Child of God can also be described as an existential text, particularly for the authenticity of its protagonist. Lester Ballard’s atavistic tendencies bring him closer to an animalistic level. From those all of McCarthy’s novels, The Road which was published in 2006 by Vintage book publisher is the most representative novel which is related to the study of Ecocriticism. The novel is generally thick of environments’ issue. The issue for instance is the fire of woods that happened along the country which give the reader an image of burned land, ash and dust everywhere and so on. Because of this reason, the writer felt that The Road is interested to be analyzed through ecological critics. In short, the novel portrays a journey of father and son as the main character in a burned land in America. The issue of devastation of earth becomes the centre point of interest which grasps the whole setting of the novel. The Road brings the readers onto ‘the future’ in as much as it is set in a time after an ambiguous ‘end’ has occurred and society has collapsed. The reverse of the most recent reissue claims that it is the first great masterpiece of the globally warmed generation. It is also the first of McCarthy’s novels to have provoked Ecocritical study. This wide appeal to the novel relies strongly on its environmental themes. The use of allusion to genre and form elsewhere in McCarthy’s novels can be said to universalise his appeal but in The Road the key concern is the 21st century’s most immediate global problem; the irrevocable damage global industrial capitalism is doing to our environment. It is difficult to read The Road without feeling the overwhelming cumulative force of the novel’s desolation, and this desolation is most prominently present in the landscapes McCarthy portrays. The setting is almost entirely bereft of life; the little that is found is often malign humanity. The Road greatly represents a study of Ecocriticism. It portrays the colourless world because of devastation of earth. This devastation issue is common object of the Ecocriticism study. The Road continually reminds us of the bleakness of the landscape in the earth. As readers, we only experience bright colours through the characters' dreams or memories, if someone happens to bruise or bleed, or through fire or flare guns. The rest of the time we see a gray ash covering the landscape. As a reality, our landscape is actually green and natural. However, The Road shows the possibility of devastation of earth when humans did devastation to the nature and they can’t live in harmony with the nature. Therefore, there is no doubt that The Road becomes the most influencing novel toward environment. It proves from the acclaim written in the novel by George Monbiot, an environmental campaigner that says "It could be the most important environmental book ever. It is a thought experiment that imagines a world without a biosphere, and shows that everything we value depends on the ecosystem." According to the brief story in background of the study that gives perception about the devastation of earth in the novel, it appears two questions as the problems: 1. How is devastation of earth depicted in Cormac McCarthy’s The Road? 2. How does devastation of earth give impacts to the main characters in Cormac McCarthy’s The Road? METHOD The used method is descriptive quality; it means the quality of the data becomes the reference to work rather than the quantity of the data. Besides, a technique is needed to understand the data. Technique of interpretation must be used to interpret and analyze the data. Through interpretation the analysis can be worked. Interpretation is a crucial step that has to do before analyzing the data. Then, extrinsic approach is used as an approach toward the analysis in which environment belongs to it. According to method above, the first thing that has to do is collecting data. In collecting data this research focuses on reading and documentation. Reading novel. In this step, novel becomes the object of the research. The novel is entitled The Road, written by Cormac McCarthy. To collect the correctly data, it needs reading more than once, because to get interpretation, it needs understanding all contents completely with all possibilities both intrinsically and extrinsically. Inventorying data. This step is collecting data through noting the quotations related to the statement of the problems and objectives of the study, it is including in words, sentences, and discourse that can represent devastation of earth in Cormac McCarthy’s The Road. Thus, all data that will be analyzed are started and sourced through the novel’s contents. Classification data. It is appropriate to the statements of the problems about devastation of earth in Cormac McCarthy’s The Road. Tabling the data. It is to simplify reading the data and classify data that is used in the analysis for the readers. Continuously, the selected data or the collected data, which are related to the statements of the problems and the objectives, are analyzed through Ecocriticism in depicting the devastation of earth and its impacts to the main characters in Cormac McCarthy’s The Road. MODERNISM The word “modern” closely means to up-to-date, abreast of the times, and going beyond the past in more than a temporally or chronologically literal sense (Greenberg, 1979; 2). Marshall Breman as quoted Jan Rada defines modernism as a trend of thought that affirms the power of human being to create, improve, and reshape their environment, with the aid of scientific knowledge technology and practical experimentation (2008; 6). Breman then argues that modernism is as any attempt by modern men and women to become subjects as well as objects of modernization, to be modern is to find ourselves in an environment that promises us adventure, power, joy, growth, transformation of ourselves and the world-and, at the same time, that threatens to destroy everything we have, everything we know, everything we are (Berman, 1982; 5; 14). The development of modernism emerged two poles that confront each other; science and technology and natural degradation. As Helena J. Keler explanation that the image of ‘creative destruction’ is very important to understanding modernity precisely because it derived from the particular dilemmas that faced the implementation of the modernist project. This destruction of a holistic universe in the modern era shatters the conception of human beings and societies as total entities, instead inaugurating an era characterized by a never-ending process of internal ruptures and fragmentations within itself (Keler, 2005: 4). According to Horkheimer and Adorno as quoted by Helena, modern capitalist society is engaged in a pattern of domination: the domination of nature by human beings, domination of nature within human beings, and this system of domination is driven by fear of the human and nonhuman unknown the Other (Keler, 2005: 3). Movement of modernism manifests itself in the self-destructive nature of symbolism: when pushed to its logical extreme, the symbolist aesthetic starts to forgo any notion of an organic, necessary relationship between signifier and signified, and simply imposes a particular motif as an arbitrary symbol of something else (Hutchinson, 2011; 58). Modernism often demonstrates the destructive rather than constructive nature. Modernists argue that the ecologically destructive projects are not viable because of climate change but modernism movement (Johnston, 2012: 207). Specifically, Barbara Rose Johnston states that Human conduct that contributes to the destruction of our ecological balance. Such interpretations of environmental change, however, can have undesirable effect of deflecting responsibility, since blame is placed on a cycle of time about which a person can do nothing (Johnston, 2012: 212). Global environmental change, which spans natural sciences, policy and development studies, is currently experiencing its first waves. Perhaps it is time to recognize that already some people are getting their feet wet. On what criteria should one decide to retreat to higher ground or stick it out unmoved until the tide turns. Modernism challenges the modern project of understanding global environmental change and doing something about it when it causes problems (Blaikie, 1996: 81). According to Piers M. Blaikie, modernism First, it challenges all embracing world views or ‘meta narratives’ which tend to be highly teleological and assume the validity of their underlying assumptions and their claims. Thus, the role of environmental scientists in policy making as ‘talking truth to power’ and as the only rational and legitimate brokers between the ‘real’ environment and the rest of us, is rejected. Second, it challenges the tendency that is more pronounced in areas of global environmental change where the local hands on experience of the environment (land degradation, desertification and biodiversity). Third, it challenged that reality is socially constructed. An epistemology which builds models of society and environment with causal connections is challenged by one which is constituted as a series of descriptive accounts according to different actors’ perceptions (Blaikie, 1996: 81). Modernism encourages people and countries to over-exploit natural resources, and contribute to reductions in spending on social and environmental welfare (Huckle, 1999: 36). Moreover, environmental reductions being blamed on the impact of foreign cultural domination this has allegedly eroded and damaged the ‘essential harmony’ between humans and nature (Mawdsley, 2001: 96). Evernden contends that the second instrumental vision of control and domination over nature is the historical product of modernity, more specifically of Renaissance, when a new mode of knowledge, based on reason and experimentation replaced the medieval search for knowledge as contemplation and wisdom (1992). This argument is supported that Modernity is thus responsible for creating Nature by abstracting from nature, and with it a whole history of conquest and domination comes to be enacted. In the words of C. S. Lewis: “We reduce things to mere Nature in order that we may “conquer” them. We are always conquering Nature because “Nature” is the name for what we have, to some extent, conquered” (Lewis, 1978: 42). Latest, Environmental problems and other risks encompass less than the globally catastrophic. More and more disaster experts, development agencies, and citizens’ groups are supporting that the globalisation is largely responsible for such human misery (Huckle, 1999: 36). Modernism signed by the development science and technology (Somerville, 2006: 17-18). Further, given the increasing production by technologically advanced capitalism of risks that threaten us all ironically that technology induced catastrophes and environmental disasters (Simon Cottle, 1998: 8). Since the Enlightenment, technology, especially science-based technology, has offered the promise of a better world through the elimination of disease and material improvements to standards of living. On the other hand, resource extraction, emissions of dangerous materials, and pollution of air, water, and soil have created conditions for unprecedented environmental catastrophe and have already caused irreversible damage to the biosphere (Vergragt, 2006: 7). Ironically, the persisting contradictions between a better life created and supported by technology for the wealthy few, also caused the increasing environmental degradation and persistent poverty for the vast majority calls for a deeper exploration and understanding of the nature. Philip J. Vergragt then, states that technology will support and enhance a “good life” for all of its citizens, in both rich and presently poor countries, without compromising the Earth’s ecosystem or the prospects of later generations (Vergragt, 2006: 8). Thus, science and technology which shaped to the sophistication give man a power to colonize the earth. POSTCOLONIALISM Environmentalism in post-colonial discourse has its beginnings in Alfred Crosby’s account of the impact of European incursions into the Americas and the Pacific (Ashcroft, 2000: 71). This incursion of course destructs not only the country; physical building and ideology but also the environment and nature. The conquest and colonization of so many extra-European environments produced irreversible changes in land use, in flora and fauna and frequently damaged beyond repair traditionally balanced relations between indigenous communities and their environments, a relationship unlike that of their conquerors crucial to their understanding of their ‘being’ as of the land rather than merely on it (Ashcroft, 2000: 71-72). He adds that imperial incursions and colonization have been regarded as environmentally destructive, yet as Richard Grove argues, the perception of what had already been lost in Europe, the sense of intrinsic connection between the ‘more-than-human’ and the human, and thus the urgency of environmental preservation became strikingly evident in Europe’s colonies, particularly in the late nineteenth century. Much environmentalism in theory and practice has emanated from former imperial centres such as Europe and the United States. While belated recognition of the crucial importance of other forms of life on earth is both welcome and necessary, its export and sometimes imposition on postcolonized cultures invites the obvious charge of hypocrisy and generates resentment against former imperial states which having degraded their own and their colonies’ environments in the ‘interests’ of progress and ‘development’ now encourage (or impose) the theory and practices of environmental preservation on other peoples (Ashcroft, 2000: 72). This also frequently creates division within post-colonized cultures themselves, where, for instance, peoples are moved off their traditional lands to make way for game parks, essentially for the benefit of wealthy tourists. Demands for the ‘global’ preservation of endangered species frequently clash with the policies of post-colonized governments eager to use their regained environmental sovereignty in the interests of a modern capitalism from which it is difficult for them to escape. Devastation of earth has highlighted how human–environmental vulnerabilities are amplified not only by anthropogenic climate change but also by the capitalist exploitation of natural resources (Carrigan, 2005: 1). Harmful environmental conduct exposes several broader dimensions such as the nation’s ability to use its resources as determined by domestic political processes, such as; it changes the natural forest microclimates that have been transformed into new microclimates increasing sunlight and lowering humidity (Nazzal, 2005: 6). The ecological crisis is not merely an isolated event but has its roots in the modern materialistic civilization that makes man becomes the butcher of earth (Huggan and Tiffin, 2010: 1). They argue that one way out of this morass is to insist that the proper subject of postcolonialism is colonialism, and to look accordingly for colonial/imperial underpinnings of environmental practices in both colonising and colonised societies of the present and the past (Huggan and Tiffin, 2010: 3) Colonialism greatly changed the environmental condition of colonized country. Alfred W. Crosby (Crosby 1986) as quoted by Aschroft describes the ways in which the environments of colonized societies have been physically transformed by the experience of colonial occupation, imperialism/colonialism not only altered the cultural, political and social structures of colonized societies, but also devastated colonial ecologies and traditional subsistence patterns (Ashcroft, 2000: 69). Indirectly, colonization influences ecological changes in the past which cause ecological destruction in the present day. More importantly, based on Crosby statement in Aschroft explain that introduced crops and livestock not between colonizer and colonized country only supported conquering armies and colonizing populations, radically colonizer altered the entire ecology of the invaded lands in ways that necessarily disadvantaged indigenous peoples and annihilated or endangered native flora and fauna (2000: 69). Arguably this has led to one of the most profound ecological changes the world has seen. Colonization or colonialism can be defined as the conquest and control of other people’s land and goods (Loomba, 2005: 8). Colonialism means a conquest which is done by the west or European and American country toward Asia and Africa by exploitation the land, surely it causes natural destruction. Elleke Boehmer has defined colonialism as the settlement of territory, the exploitation or development of resources, and attempts to govern the indigenous inhabitants of occupied lands (Boehmer as qtd. in McLeod 2000: 8). The term colonialism is important in defining the specific form of natural exploitation that developed with the expansion of Europe over the last 400 years (Ashcroft, 2000: 40). With the end of the cold war, global infatuation with neoliberal economics has intensified the peripheralization of the South along economic, political, social, cultural and natural lines (Geeta Chowdhry and Sheila Nair, 2002: 1). Postcolonial critique bears witness to those countries and communities - in the North and the South (Bhabha, 1994: 6). The assumption of postcolonial studies is that many of the wrongs, if not crimes, against nature are a product of the economic dominance of the north over the south (Young, 2001: 6). Thus, the Norh represents the West and the South represents the East. Postcolonialism sees the natural destruction on the South as the impacts of colonization The northern environmentalism considered as the rich (always potentially vainglorious and hypocritical) and the southern environmentalism considered as the poor (often genuinely heroic and authentic) (huggan and Tiffin, 2010: 2). However, northern needs of the natural need were supplied from the south in the name of colonization. Colonialism granted imperial powers the rights to arrogate and exploit the territory of a subject people as well as to appropriate unlimited property rights, post-colonial states acted quickly to regain control over their natural resources both through expropriation of foreign property interests and through the legal arena (Nazzal, 2005: 10). Colonialism, through both practice and discourse, has separated man from his natural surroundings and has given him a false idea about the meaning of nature: on the contrary, nature is not there to be plundered, but to be cared for, tended and made to yield its produce. Then, Man is ennobled by the relationship with the environment, by his power to make things grow and watch over their growth, but the reverse also holds true: devastation returns man to his primitive condition. It is not surprising when the the nature did reverse destruction to the humans. It is the result of what they do exploit to the nature. On the other world, man as the colonizer has colonized the earth which caused the devastation of earth. (Chrisman and Williams, 1994: 1–20). Thus, postcolonialism can be considered as umbrella term of ecocriticism in which it criticizes the relation between human and nature including criticizing humans’ behaviour precisely humans’ exploitation toward nature. ECOCRITICISM Humans truly can’t be separated with environment. human beings are engaged in the eternal search for connection, for that which connects us to others and for that which connects us to ourselves, culture, language, history, belief systems, social practice, and other influences on human development are as much a part of place as the physical landscape one crosses (Dreese, 2002; 2-3). She emphasizes that environmental factors play a crucial role in the physical, emotional, and even spiritual configurations that determine our ideas of who we are. All human beings develop their own sense of place through life that determines why they love certain regions or feel utterly alien in others. The study of relations between humans and environment called ecology. Lawrence Buell defines ecology as the study of the interactions between organisms and the environment (Buell, 2005; 139). Meanwhile, Glen A Love defines ecology as not as merely a study of the relationship between organisms and their living and nonliving environment but also a combination of science and a sense of responsibility for life (2003; 37-38). Ecology as Lawrence Buell say above is drawn in the life circle; the life processes of many organisms put into their surroundings environment whose presence of other organism affects the life processes of these and other organisms sharing the same environment. When these processes are cut by such destruction, e.g. chemical by-products of the life processes of one species (or occupational group) are harmful to another species; the relationship between the two species is "antagonistic." Increased population density increases the probability of antagonistic interactions (Catton, 1994: 80). It is essential to be aware of the environmental damage which caused by ecological changes. The development of humans’ ecology slowly damages the environment. The ecology of human development involves the scientific study of the progressive, mutual accommodation between an active, growing human being and the changing properties of the immediate settings (Bronfenbrenner, 1979: 21). Imbalance fine relations between humans and environment emerged a critic called ecocritic or ecocriticism (Buell, 2005; 2). John Elder as quoted by Dana Philip says that The science of ecology confirms the indivisibility of natural process: each feature of a landscape must be understood with reference to the whole, just as the habits of each creature reflect, and depend upon, the community of life around it (1999; 581). Ecology when it counts as science tends to be a lot more reductive, thus many of the core concepts of ecology once notable for their expansiveness have in recent years been cut down to size, made more particular, or abandoned altogether. It now appears that even the ecosystem concept may not be valid biologically, but valid concept or not, an ecosystem is primarily a theoretical entity, and therefore could never be the reality that somehow underwrites poetry, even if that poetry is of the good old-fashioned, supposedly "organic" sort (Philip, 1999; 582). By that kind of reason, Elder argues that culture too may be understood organically: it is the field of relationship between organisms and, as such, a complex organism in its own right (Philip, 1999; 582). Ecology is not merely bound to science and technology, but also moral and politic. Greg Garrard assumes that ecology itself is shifting and contested, the emphasis on the moral and political orientation of the ecocritic and the broad specification of the field of study are essential (2004; 4). Problems of ecology are features of our society, arising out of our dealings with nature, from which we should like to free ourselves, and which we do not regard as inevitable consequences of what is good in that society (Garrard, 2004; 5). Lynn white, Jr argues in his article on Cheryll Glotfelty’s The Ecocriticism reader: landmark in literary ecology that environmental crisis is fundamentally a matter of the beliefs and values that direct science and technology and dominating attitude toward nature (1996; 4). Discoveries in ecology and cellular biology revolutionize our sense of self, teaching us that there is no such thing as an individual, only an individual-in-context (Neil Evernden, 1996; 93). Discoveries of course get much of invention. Unconsciously, humans’ behaviour (ex: exploitation) toward environment was changed. Industrial Revolution affected humanity's conception of its relationship to nature, warning that technology has created the false illusion that we control nature, allowing us to forget that our "unconquerable minds” are vitally dependent upon natural support systems (Harold Fromm, 1996; 31) Ecocritic or Ecocriticism is an umbrella term, used to refer to the environmentally oriented study of literature and (less often) the arts more generally, and to the theories that underlie such critical practice (Buell, 2005; 138). Cheryll Glotfelty simply writes the definition, ecocriticism is the study of the relationship between literature and the physical environment, ecocriticism takes an earth-centered approach to literary studies (1996: xviii). Ecocriticism might succinctly be defined as study of the relation between literature and environment conducted in a spirit of commitment to environmental praxis (Lawrence Buell as quoted by Dana Philip, 1999; 583). Ecocriticism is, then, an avowedly political mode of analysis, ecocritics generally tie their cultural analyses explicitly to a ‘green’ moral and political agenda. In this respect, ecocriticism is closely related to environmentally oriented developments in philosophy and political theory (Greg Garrard, 2004; 3) Ecocentrism is more compelling as a call to fellow humans to recognize the intractable, like-it-or-not interdependence that subsists between the human and the nonhuman and to tread more lightly on the earth than it is as a practical program (Lawrence Buell, 2005, 102). Ecological criticism shares the fundamental premise that human culture is connected to the physical world, affecting it and affected by it. Ecocriticism takes as its subject the interconnections between nature and culture, specifically the cultural artefacts of language and literature (Cheryll Glotfelty, 1996; xix). The majority of ecocritics, whether or not they theorize their positions, look upon their texts of reference as refractions of physical environments and human interaction with those environments, notwithstanding the artifactual properties of textual representation and their mediation by ideological and other socio-historical factors (Lawrence Buell , 2005; 30). Literary theory, in general, examines the relations between writers, texts, and the world. In most literary theory "the world" is synonymous with society-the social sphere. Ecocriticism expands the notion of "the world" to include the entire ecosphere or nonhuman, which is physical environment. Several things that have to be seen are: • Transforming this concept becomes social movement that will bring the humans into conscious of the equality between human and their environment and doesn’t consider the nature into binary opposition between dominate and dominated. • Ecocriticism encourages the changing of canonisation through entering literary works which carry up natural issue. • Ecocriticism is not only an approach but also a pendadogis tool. • Ecocriticism connects the literary study with the earth to see how is the relation between humans and earth where they stand (Cheryll Glotfelty, 1996, xxii) The majority of ecocritics, whether or not they theorize their positions, look upon their texts of reference as refractions of physical environments and human interaction with those environments, notwithstanding the artifactual properties of textual representation and their mediation by ideological and other sociohistorical factors (Buell, 2005; 30). It can be assumed that Ecocrtiticism sees the text as the refraction of physical environment. Another denigrates attempts to recuperate realism as restricting the field of environmental writing, as ludicrously foreshortened in focus (“its practitioners . . . reduced to an umpire’s role, squinting to see if a given depiction of a horizon, a wildflower, or a live oak tree is itself well painted and lively”), and in any case bogus, since “mimesis presumes the sameness of the representation and the represented object” (Phillips 2003: 163–4, 175). Buell has added that this is a conviction that contact (or lack ofcontact) with actual environments is intimately linked, even if not on a one-to-one basis, with the work of environmental imagination, for both writer and critic (Buell, 2005; 31). Ecocriticism can explore what we can call a discursively manipulated nonhuman world in literature, and discuss how it gets marginalized or silenced by, or incorporated into the human language (Legler, I997: 227). Nonhuman environment must be represented as an active presence and player within the text made some astute readers inclined to be sympathetic of the environment (Buell, 2005: 51). The task of ecocriticism, then, is to formulate a conceptual foundation for the study of interconnections between literature and the environment. Literature can be perceived as an aesthetically and culturally constructed part of the environment, since it directly addresses the questions of human constructions, such as meaning, value, language, and imagination, which can, then, be linked to the problem of ecological consciousness that humans need to attain. Within this framework, ecocritics are mainly concerned with how literature transmits certain values contributing to ecological thinking (Glotfelty, 1996: xxi). Ecocriticism offers researcher a way how to analyze such literary work through three steps. First is seeing the representation of nonhuman aspect. This first step is looking how is the nature like rice field, village, wilderness, forest, sea, beach, hill, mountain, valley, river, animal (or treatment toward animal) and city environment pictured in the text. Second is seeing the accusation toward ecology issues. The second step destructs how the natural issue is portrayed with the different way. For instance, the nature is pictured as an inconvenient place again for humans because of the emergence the new value; technology, capitalism, extinction of local knowledge, and development of building which is not oriented to the environment. Last is taking part of text’s ideology. In this case examines the relations between writers, texts, and the world. This third step is seeing and taking part of the ideology that contains in the text. How the author’s view and commitment toward the nature (Cheryll Glotfelty, 1996, xix). DEVASTATION OF EARTH Those all theories mentioned above are related to the word “devastation” which happened on earth. Modernism granted colonizer a power to devastate the earth in which postcolonialism and ecocriticism tend to criticize that devastation. Certainly, what is actually the meaning of devastation of earth? The word “devastation” itself according to Merriam-Webster dictionary means the state or fact of being rendered nonexistent, physically unsound, or useless. In other word, devastation is deterioration, destruction, vanishing of the earth through depletion of resources such as air, water and soil. Devastation of earth can be defined as a destruction of ecosystems and the extinction of wildlife. Devastation of earth is a term used to describe a situation in which a part of the natural environment (the earth) is devastated or damaged. According to Shakhashiri, earth is areas of land as distinguished from sea and air (2011: 1). It means that the earth is composed by three parts; land, sea and air. Thus, it can be ascertained that if the devastation happened on earth, it will strike those all of earth’s parts. The devastation which strikes the air will harm the condition of air in the atmosphere or known as devastated atmosphere, devastation which strikes the land will harm the condition of the soil and change it into erode and barren, and devastation which strike the water will contaminate the clean water into the dirty one. The earth as mentioned above that composed from three parts; certainly those each parts have a role. Land is the surface of the earth where the creatures are growing and developing; the plantations (trees) grow well, the animals breed and the humans dwell the life. Air is the mixture of gases which surrounds the Earth in which it contains a lot of vital substances such as oxygen and ozone. And water is a clear liquid, without colour or taste, which falls from the sky as rain and is necessary for animal and plant even human life. Water is also available in the river and sea. All of those parts of the earth greatly have advantage when it states in the normal/natural condition. However, when it was devastated, the earth turns into less natural and more miserable. That is the picture of the devastation of earth. DEPICTION OF DEVASTATION OF EARTH The devastation of earth as Hughes says has happened in every historical period and in every part of the inhabited Earth (2001: 1). It means that devastation of earth happened in the whole surface of the earth. Devastation has stroked the whole environment; atmosphere, land, and sea. Postcolonialism argues that colonialism has an intervention on devastating the earth. Colonialism has devastated the earth as Ashcroft says that the conquest and colonization of so many extra-European environments produced irreversible changes in land use, in flora and fauna and frequently damaged beyond repair traditionally balanced relations between indigenous communities and their environments (2000: 71-72). He adds that imperial incursions and colonization have been regarded as environmentally destructive. Devastation of earth happened over earth. It means that devastation happened on land, atmosphere and sea. The land has changed into gullied, eroded and barren. This changing surely as the impact of devastation of earth which is done by the colonizer in colonizing the land. Everything which stands on the land has changed, There was no reborn flora and fauna in McCarthy’s The Road. However, the presence of the flora and fauna is the rest of the previous world. Indeed these flora and fauna have changed as the impact of colonialism. Flora in McCarthy’s The Road is dominated by the trees. However, most of the trees have changed into gray, dark and black. It is so pathetic when the father and his son faced the standing black trees and they realized that it changes. Horribly, it seems like ghost of trees. The changing of the trees is not underlined on the changes of its colour but also its presence. It means that the trees are not only changing into dark and black with its standing but also there are many trees which die and fall to the ground. The changes of fauna can be seen when the father and his son was camp in the forest and listening for any sound, it draws that the bird has changed its behaviour by holding migratory to circle the earth. The birds can no longer life in harmony with the environment by occupying the forest. It is caused the changing of trees which turn into dead. Thus, it forces the birds to change themselves. Other fauna changing draws when the father who found an odor of cows. However, the cows are extinct since years ago. He asked to himself whether the cows are really real or not. He finally realized that it is extinct. It shows that the cows are changed from the presence to absence. The burning of a certain thing; such as the trees, surely produces a residue or combustion. It can be carbon and ash. It can be imagined how large the amount of ash will be produced if the whole land of forest were burned. Certainly, the ash will cover everything that has seen. A horrible fire of forest has produced a horrible ash too till everything is covered by ash. The ash has moved along the wind till it covered the city and everything in the city, The fire of forest makes the amount of ash become uncontrolled. The moving of ash filled the air and atmosphere in which it makes everything coloured covered by ash and dust. Hence, everything becomes colourless. The ash changes the landscape become gray. It can be assumed that the graying landscape is no other causing by the moving ash. The occupying of ash in the atmosphere makes the day become unseen and dark. The result of the residual combustion is not ashes merely, but also carbons that harm the environment. Ash and carbon both fill and occupy the atmosphere. As the greenhouse effect idea, that the ash and carbon also dust which in a large amount and uncontrolled in atmosphere will form a mantle which wrapped out the whole of earth. This causes our sight of the sky become dark and gray.The sky and cloud are devoured with ash. The cloud becomes ashen and gray. Severity, the ash and carbon have contaminated everything in the air including the sea water vapor. Then, the result is clouds of ash. Ash and dust have affected the form of the cloud to become gray. Probably its content has been also affected. When the clouds changes into gray, it can be predicted that the rainwater which come down from the clouds will also be gray. It is supported with the presence of the ash mantle that wrapped up the earth. Certainly, everything which come down from the sky; rainwater has to pass this mantle, consequently the rain water will be coloured as gray by the ash mantle. The ash mantle has coloured the rain water. The rainwater which drips down to the earth is seen as the gray sheets of rain. Rainwater that is usually used by humans to fulfil their needs such as to irrigate the fields has been contaminated by ash and carbon so that its contents no longer can be used for the benefit of man. Consequently, there will be no crops and there will be no natural food. Mantle of ash has blanketed the earth during the unknown time. As described above that everything which fell from the sky will pass this mantle so that everything will be contaminated by it. The result, everything which fell will be gray. After several days the father and his son watched the gray sheets of rain, the weather quickly changes into snowy. Everyone knows as it has seen that snow is falling from the sky. The snow actually is similar to the rain, including their formed and their fell. The sea water vapor which is formed into cloud in the sky will fall as the rainwater, however, because of the extreme/cold weather, the rain water freeze into ice and it changes into snow that is white and soft. This falling snow of course has to pass the mantle of ash and it changes into gray. The next devastation of earth is turned to everything which lay on the surface of the earth covered by darkness as the ash effect. Everything stands in the earth turned to be black such as the dead trees which burned by fire forest, and the rain water and snow which fell as gray turn into black in the land. The dead trees which burned by fire forest surely create a black view of trees. The trees which burned in incompletely will make an appearance of burnt and black trees. The rainwater and snow which are grey in their falling turned to be black in the land. The large number of those rainwater and snow gathered as one in the ground create a new colour, more intense and black. The gray flakes which fell down turned to the dark slush. Dark slush can be assumed as the slush which is thicker than a flake. Thus, the slush which is as the result of flakes changes into black. It is also applied in the rainwater; the water in the land is not the whole from the rainwater, some from the river and so on. However, the thick rainwater which fell down in gray proved that its water is dominated to black water. the slush which is melted flows through the ash and turned to the black water. THE IMPACTS OF DEVASTATION OF EARTH ON FATHER’S ATTITUDE Living and dwelling in such devastated earth surely give impacts to the humans who walk over it. The father and his son reveal those kinds of impacts. The father who lived before and after unknown disaster seems undergoing a lot of impacts. It is different with his son who born after that disaster. He tends to be innocent, only watch and observe what his father did. There was an idea to end the life when the father still lived with his woman. She always forces him to end their life because there was nothing else to do in the ruined world. However, the father keep his believe that humans have to struggle. The experience of dwelling the life before the unknown disaster made him stronger. The father realized that what the environment did to him is the result what the humans did to the environment, as Lawrence Buell says that human culture is connected to the physical world; nature and environment, affecting it and affected by it. In other word, humans have affected the environment and have been affected by environment. The woman forces him because they lived in unusual life, they lived like zombie. The devastation of earth causes their life as like as zombie or walking dead in a horror film which the father and his son have a role as the victims. They have to avoid even to face the zombie to keep alive. Dwelling the life in such devastated earth; the air was filled by the ash and dust forces them to wear a mask. The devastated earth; unfriendly air forces him to wear mask (canister mask) and even wear biohazard suit. As the affection of the devastated earth, the father and his son have to worry their life, Mostly he worried about their shoes. Worrying is something that the father in his son has to do. There is no certainty living in such ruined world. It is a common thing for them to worry anytime, worrying of food and shoes. Food is essential thing to keep alive. It is the reason why they worry of food. If they can’t find some foods, it means they will die. The shoes are important stuff to hold a journey. As explain before that the weather extremely changes a while. Few days were raining, and another was snowing. Shoes keep the father in his son feet to keep away from coldness and freezing which can take their life. The weather is extremely cold. It is not surprising that the weather turns to colder and colder. The weather has changed anytime; sometime it rains and often snow. The coldness of weather doesn’t only force them to eat the food that already fermented as above but also threaten their life. The coldness is very extremely danger for them. Moreover it is pictured that the cold can crack the stone and takes their life off. In such condition surely makes them hard to breathe because in the coldness the air contains thin oxygen. Dwelling the life in such devastated earth actually makes him aware of surrounding even the weather. The sounds like forest fire, fallen trees, and so on makes his ears disturbed and consequently he has to keep awake. Living in such devastated earth makes him to be more aware toward everything that threatens them. The father and his son have experienced many kinds of problems. Everything that happened to him does not break his spirit to keep alive even when they are in starving. He always believes that he would find something to eat. the father always optimistic dwelling life. the devastated earth makes him become more optimistic. Struggle is a must to do to find another thing to be eaten to keep the life. Keep trying is the key for the good guys who living in the ruined environment. By keeping trying, they can survive dwelling the life in such environment. Keep trying is not enough to live in such devastated earth. Always suspect the possibility that may happen has to be done, because no one knows what will happen, but the threat of nature always happen all the time. Thus, another thing that has to do is to remain vigilant about the environment. The devastated earth forces him to become “cautious, watchful” and always “on the lookout”. He believes that no one expect a trouble. However, living in the devastated earth, the thing that has to do is to always expect it. Thus he was always wary of something bad that may happen. Nothing can be expected from the nature. The father always believed it. He no longer agrees if people prepare something for tomorrow. Although he always optimistic of what he did, he never believed it. For him, even though he's preparing for tomorrow, he doesn’t believe that the nature will prepare for him. What the father believes that is now or tomorrow is the same. This belief keeps the father spirit to face his following days. As a father he would often feel the pain. Physically, he is ill of facing the devastated earth. And mentally, he is ill of the feeling of bearing the responsibility as a father who is responsible for the survival of his son and his own life. However nature should never take the life of his son. He would bet his life for the life of his son. Often he complains to himself about his illness. He pretends as tough man in front his son but actually he felt tremendous pain. It’s just that he does not want his son to know. THE IMPACTS OF DEVASTATION OF EARTH ON SON’S ATTITUDE Being born in the devastated earth which the unknown disaster has swept it surely affects the son’s behaviour toward environment. The greyscale image of environment has saved well in his mind that forces him to expect something else, something in colour. When they continue their journey, the son had found some crayons. These crayons change his mind that something left on earth in colour. Thus, environment is not filling of gray merely. The crayons seem like a hope for